Vulnerable Narcissism and Social Anxiety Disorder: Similarities and Differences - Dilay ELDOĞAN; Ezgi TUNÇEL (Nesne Psikoloji Dergisi, 2017)
According to literature and clinical observations, there are some similarities and differences between social anxiety disorder (SAD) and vulnerable narcissism (VN). However, there exist only a limited number of research but on this topic. Thus, in the current study, it was aimed to investigate the similarities and differences in terms of perceived parenting and compensation focused coping styles among groups with low, moderate and high levels of SAD and VN. Parallel with the aim of the study, 357 participants (age: M = 25.72, SD = 9.64; 235 (65.5%) female and 123 (34.5%) male) were examined in terms of their SAD and VN symptoms and they divided into three groups such as high, moderate and low symptom level groups. Then, the groups were examined in terms of their perceived parenting and compensation focused coping styles. According to the results of the study, it was found that whereas high VN symptom level group scored higher in terms of controlling and belittling mother parenting styles than low VN symptom level group, high SAD symptom level group scored higher in terms of controlling mother, belittling mother, and overprotective mother and father parenting styles when compared to low SAD symptom level group. Moreover, high VN symptom level group tended to use more all of the compensation focused coping styles when compared to low VN symptom level group. On the other hand high SAD symptom level group did not differ in terms of the level of using compensation focused coping styles from low SAD symptom level group. In the light of the findings of the study, it was proposed that one of the distinctive features between VN and SAD can be the coping styles that the individuals are applied in their daily lives, and that finding can guide both the clinical applications and research.